2014
DOI: 10.7567/apex.7.031602
|View full text |Cite
|
Sign up to set email alerts
|

Crossbar arrays of nonvolatile, rewritable polymer ferroelectric diode memories on plastic substrates

Abstract: In this paper, we demonstrate a scalable and low-cost memory technology using a phase separated blend of a ferroelectric polymer and a semiconducting polymer as data storage medium on thin, flexible polyester foils of only 25 µm thickness. By sandwiching this polymer blend film between rows and columns of metal electrode lines where each intersection makes up one memory cell, we obtained 1 kbit cross bar arrays with bit densities of up to 10 kbit/cm 2 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 18 publications
0
25
0
Order By: Relevance
“…Memory diodes have been reported that were based on phase separated blends of P(VDF-TrFE) and organic semiconducting polymers. [23][24][25][26] The structure of these blends consists of semiconducting columns in a ferroelectric matrix. The bi-stable polarization state of the ferroelectric yields the binary information that can non-destructively be read out by current through the semiconducting columns.…”
Section: Introductionmentioning
confidence: 99%
“…Memory diodes have been reported that were based on phase separated blends of P(VDF-TrFE) and organic semiconducting polymers. [23][24][25][26] The structure of these blends consists of semiconducting columns in a ferroelectric matrix. The bi-stable polarization state of the ferroelectric yields the binary information that can non-destructively be read out by current through the semiconducting columns.…”
Section: Introductionmentioning
confidence: 99%
“…The cross-talk problem can be avoided by integrating rectifying diodes or transistors, which are electrically connected in series with the resistive memory elements [16,17]. Alternatively, the memory element itself could be rectifying [4,13,14], but most examples of multilevel elements found in the literature are not.…”
Section: Introductionmentioning
confidence: 98%
“…The simplest layout for an integrated collection of memory devices is a passive matrix array in which the active materials are sandwiched between two electrodes in a cross-bar geometry [13,14]. Such passive memory arrays feature the maximum density of memory elements as each cell occupies an area of only 4f 2 , where f is the feature size (meaning the electrodes' width as well as spacing between cells).…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] Solution-processed organic ferroelectric resistive switches have recently been proposed as a very promising practical realization of a non-volatile memory that can be read out non-destructively and is compatible with flexible electronics and large area applications. [3,4] The organic ferroelectric resistive switch consists of a thin film made of a polymeric semiconductor-ferroelectric blend sandwiched between two electrodes. The phase separation in the blend is driven by a spinodal decomposition process which results in sub-micron sized semiconductor domains embedded in an insulating ferroelectric matrix.…”
Section: Introductionmentioning
confidence: 99%